A novel algorithm for optimal sizing of stand-alone photovoltaic pumping systems - Asmae Hafian; Mohammed Benbrahim; Mohammed Nabil Kabbaj (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Pumping water is one of the most popular technologies of solar energy for irrigation or drinking water supply. Its performance depends on the characteristics of the site (sunlight, ambient temperature, geographical obstacles), on the performance of the modules, as well as, on the characteristics of other equipment (converter and pump). The optimal sizing of a photovoltaic water pumping system makes it possible to guarantee the satisfaction of the water demand throughout the irrigation period and to model the electrical energy needs to supply the pump to irrigate the crops and water livestock. This paper proposed a novel algorithm for dimensioning the elements of an autonomous photovoltaic system equipped with irrigation water storage. The proposed algorithm determines the optimal surface area of the photovoltaic modules and the electrical power necessary to satisfy the water requirement for irrigation in the observed time. The results obtained from the proposed algorithm for optimal sizing are compared to calculation scenarios to show better results. A case study from the Fez-Meknes region in Morocco has been selected for applying the optimal sizing algorithm.